Social Status in Norway and the Law of Jante: An Analysis of ISSP Social Inequality Data - Daniel R. PALAMARA (European Journal of Interdisciplinary Studies, 2016)
This study examines International Social Survey Programme data from the 1999 social inequality module for evidence of Janteloven (‘the law of Jante’) in Norway – a widely known though often disputed description for aspects of Norwegian (and Scandinavian) society relating to equality, norming and envy. Income equality and social status were examined using survey data across 26 countries. Norwegian respondents did not show a marked preference for income equality when asked to consider the actual and deserved income of high- versus low-status occupations. However, they did stand out in reporting a distinctly and significantly smaller mean difference in social status between a high-status occupation (the chairman of a large national corporation) and a low-status occupation (an unskilled factory worker). Linear regression shows that the attitude towards social status is affected by the respondent’s level of education, but not by other personal factors. These attitudes could potentially be attributed to Janteloven, and are considered alongside the results of a small (n=30) online survey as well as popular media and academic portrayals.